Reasons of Missed Nursing Care From the Viewpoints of Nurses in Educational, Private, and Social Security Hospitals in Urmia-Iran in 2018 - Solmaz Rezaee; Esfandyar Baljani; Aram Feizi; Parvin Delnavaz (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Missed nursing care is defined as required care that has been delayed, partially completed, or not completed at all. Objectives: This study aimed to investigate the causes of missed nursing care from the viewpoints of employees in public, private, and social security hospitals. Methods: This descriptive-analytical study was conducted on 453 nurses working in five educational hospitals, four private hospitals, and a social security hospital in Urmia in 2018. Regarding data collection, the "missed care questionnaire" was distributed to nurses by convenience sampling method. The validity of the questionnaire was confirmed by the faculty members of Urmia Azad University, and the reliability of the questionnaire was assessed using Cronbach's alpha (0.9). The results were analyzed using descriptive statistics, one-way analysis of variance (p<0.05), and SPSS software version 16. Results: The most common reasons for missed nursing care in educational, private, and social security hospitals were the patients' emergency conditions (42.9%), the insufficient number of nursing assistants (38.7%), and an unexpected increase in the number of patients (18.5%). Moreover, the causes of missed nursing care in all three areas of communication, financial, and human resources were significantly different between educational, social security, and private hospitals (p=0.0001). Conclusion: Lack of nursing staff, patients' emergency conditions, and an unexpected increase in the number of patients are the main reasons for missed nursing care in educational, social security, and private hospitals. Therefore, it is recommended to apply appropriate policies to provide nursing staff, manage the admission, transfer, and distribution of patients to the hospital.